Training on Baung Fish (Mytus Nemurus) Hatchery Techniques for Fish Cultivators in Palembang City, South Sumatra Province - Muslim, Boby; Heryadi, Heryadi; Trismawanti, Ike; Helmizuryani, Helmizuryani; Khotimah, Khusnul; Harmilia, Elva Dwi; Puspitasari, Meika; Ma’ruf, Irkamiawan (Altifani Journal: International Journal of Community Engagement, 2021)
Catfish (Mytus nemurus) is a local fish with high commercial value and used as a food raw material for the traditional food in South Sumatra called pindang. The training aimed to enhance the Fish Farmer Group (Pokdakan) skills in Palembang City, which is part of community service at the Muhammadiyah University of Palembang. The method is divided into two, i.e., presented material and demonstrations, followed by a training program on Mytus nemurus breeding. The training was to produce catfish larvae, increase Pokdakan skills to produce catfish fingerling that improves the economic welfare of aquaculture actors, and increase Pokdakan's awareness of sustainable local fish production.